Dopant-free fluorene based dimers linked with thiophene units as prospective hole transport materials for Sb2S3 solar cells - Juneja, Nimish; Jegorovė, Aistė; Grzibovskis, Raitis; Katerski, Atanas; Daskeviciene, Maryte; Malinauskas, Tadas; Vembris, Aivars; Karazhanov, Smagul; Spalatu, Nicolae; Getautis, Vytautas; Krunks, Malle; Oja Acik, Ilona (Royal Society of Chemistry, 2024)
Novel dopant-free dimers comprising methoxydiphenylamine substituted fluorene derivatives and connected by central cores consisting of different numbers of thiophene moieties were synthesized and explored as hole transport materials (HTMs) in Sb2S3 absorber solar cells. Energy level diagrams show agreeable band offsets validating the compatibility of novel HTMs for the FTO/TiO2/Sb2S3/HTM/Au solar cell with TiO2 and Sb2S3 layers deposited by ultrasonic spray. X-ray photoelectron spectroscopy (XPS) study reveals the Sb 3d core level peak shift upon applying any of the HTMs on Sb2S3 indicating an increased electron density surrounding Sb atoms which refers to the interaction of S from electron-rich thiophene units with Sb in the absorber at the Sb2S3/HTM interface. It is demonstrated that application of HTMs containing diphenylamine units in their side fragments increases the cell open circuit voltage from 478 mV to 673 mV, fill factor from 46% to 56% and conversion efficiency from 1.9% to 4.5% as compared to the device without any HTM and the observed improvement can be explained by the passivation of the interfacial states. In contrast, no enhancement in device performance has been observed when applying HTMs containing triphenylamine units although strong Sb-S interaction has been detected at the Sb2S3/HTM interface. Quantum chemical simulation results suggest that to achieve enhanced charge selectivity by the organic HTM layer, the HOMO of the HTMs should be formed by the thiophene groups. Possible phenomena occurring at the Sb2S3/HTM interface are discussed providing new insights towards understanding the charge transfer at the Sb2S3/HTM interface. © 2024 The Royal Society of Chemistry.
The "Development of Semi-Transparent Bifacial Thin Film Solar Cells for Innovative Applications" benefits from a 999372 grant from Iceland, Liechtenstein and Norway through the EEA Grants. The aim of the project is to develop a new approach based on novel materials and structures and production technologies, which are the key to further increasing the share, and range of application of PV in areas with sub-average sunlight, including Baltic and Nordic countries. Therefore, development of resource saving, cost-effective and efficient PV devices is a primary challenge of this project. The project contract no. with the Research Council of Lithuania (LMTLT) is S-BMT-21-1 (LT08-2-LMT-K-01-003). Department of Materials and Environmental Technology, Tallinn University of Technology has received funding from the Estonian Research Council, projects PRG627 "Antimony Chalcogenide Thin films for Next-Generation Semi-transparent Solar Cells Applicable in Electricity Producing Windows" and PSG689 "Bismuth Chalcogenide Thin-Film Disruptive Green Solar Technology for Next Generation Photovoltaics". The research was partially funded by the European Union's Horizon 2020 ERA Chair project 5GSOLAR (grant agreement no. 952509). The research was supported by the European Cooperation in Science and Technology (COST) project RENEW-PV (CA21148) and by the Estonian Ministry of Education and Research (project TK210; TK210U8 \u201CCenter of Excellence in Sustainable Green Hydrogen and Energy Technologies'). Institute of Solid-State Physics, University of Latvia has received funding from the European Union's Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement no. 739508, project CAMART.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics